PENGARUH SISTEM INFORMASI AKUNTANSI, SISTEM PENGENDALIAN INTERN DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH DENGAN FAKTOR EKSTERNAL SEBAGAI PEMODERASI (STUDI KASUS PADA PEMERINTAH DAERAH KABUPATEN MAGELANG) - Nurendah Ragillita Untary; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to determine the effect of accounting information systems, internal control systems, and human resource competencies on the quality of the region 's financial statements using the external factors as moderation. The population in this study were all employees of the local government district of Magelang. The sample in this study was 100 respondents, namely finance and accounting staff in work units (SKPD) Magelang. Data were collected by using questionnaires and interviews. The research proved that all independent variables accounting information systems, internal control systems, and human resource competencies have positive effects on the local government financial statements while external factors do not moderate the influence of variables accounting information systems, internal control systems and human resource competencies to the quality of local government financial statements.